Improved Fetal Hemoglobin With mTOR Inhibitor–Based Immunosuppression in a Kidney Transplant Recipient With Sickle Cell Disease. Issue 8 (30th March 2017) - Gaudre, N.; Cougoul, P.; Bartolucci, P.; Dörr, G.; Bura‐Riviere, A.; Kamar, N.; Del Bello, A.
Abstract : Fetal hemoglobin induction is a key point in the management of sickle cell disease (SCD). We report the case of a kidney transplant recipient with SCD who was treated with everolimus, a mammalian target of rapamycin inhibitor. At 10 months after initiating therapy, the patient's fetal hemoglobin level was dramatically increased (from 4.8% to 15%) and there was excellent tolerance to treatment. Abstract : A kidney transplant recipient with sickle cell disease experiences a major increase in fetal hemoglobin after the introduction of a mammalian target of rapamycin inhibitor.